First Report of the Synthesis, Characterization, DFT Calculations of the New Oxoethyl Methacrylate and o-Acetamide and Evaluation of Antimicrobial, Antibiofilm and Antioxidant Effect - Cankaya, Nevin; Korcan, Safiye Elif; Turan, Nevin; Aydın, Büşra; Tanis, Emine (Taylor & Francis Ltd, 2022)
In this study, 2-chloro-N-(2-methoxyphenyl)acetamide (o-acetamide) and 2-(2-methoxyphenylamino)-2-oxoethyl methacrylate (2MPAEMA), which is unreported in the literature were synthesized and characterized. Characterization of the 2MPAEMA and o-acetamide were performed by elemental analyses, FT-IR, H-1 and C-13 NMR spectroscopic techniques. Global reactivity descriptors such as HOMO-LUMO gaps and chemical hardness, electronegativity, chemical potential, electrophilicity index, as well as NBO, MEB analyzes were performed at the DFT/B3LYP/6-311++G(d,p) level and interpreted in detail. From the theoretical results, in parallel with the experimental results, it was concluded that the o-acetamide compound had greater stability and lower toxicity than the 2MPAEMA compound. In biological studies, in vitro antioxidant activity was explained by DPPH. Agar-well diffusion effect and disk diffusion method were applied to determine the antimicrobial effect, and the effect on biofilm formation was investigated. The both compounds were found to have the high antifungal (isolated from herbal sources; Trichoderma longibrachiatum, Fusarium solani, Penicillium janthinellum and Mucor plumbeus). But only o-acetamide was found to have the antibacterial activity. The both compounds have a very high scavenging effect on free radicals. There is a need for the development of new nontoxic antimicrobial agents that can be used in agriculture around the world that do not endanger public health. We think that these substances can be used as fungicidal in agriculture.
Keywords: Antibacterial; antibiofilm; antifungal; antioxidant; 2-(2-methoxyphenylamino)-2-oxoethyl methacrylate; DFT; Ft-Ir; Polymers; Mechanisms; Biofilms; Nmr